ANALISIS PENERAPAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO. 44 TERHADAP PENGEMBANGAN REAL ESTAT PT. BUANA CIPTA PROPERTINDO - Yentina Siregar (EQUILIBIRIA, 2019)
Abstract The purpose of this study is to find out whether the Application of Real Estate Accounting PT. Buana Cipta Propertindo is in accordance with the Statement of Financial Accounting Standards (PSAK) No. 44. Development of real estate projects that can be seen from the recognition of income and costs. From this research, it is expected to be able to find out directly on the field practice about the application of PSAK No. 44 to real estate development activities.            The results of the analysis show that PT. Buana Cipta Propertindo is a real estate company that uses the full accrual method as a method of recognizing income, on the borrowing costs PT. Buana Cipta Propertindo includes these costs into the internal receivable account that should be included in the activity costs real estate development. The commission and maturation fees of the company do not group into land acquisition costs because the land used is not owned by the developer and so far PT. Buana Cipta Propertindo has developed real estate projects from vacant or new land. PT. Buana Cipta Propertindo includes the cost of public infrastructure buildings that are only in the form of public roads, roads and markets where in PSAK No. 44 there must also be schools and places of worship. For the cost of constructing public facilities that can be commercially implemented, real estate development activities carried out by PT. Buana Cipta Propertindo have inequality with the implementation described in PSAK No. 44, because there has never been a general sale of sales advice on the project. Keywords: PSAK NO. 44, Revenue Recognition, and Cost.